Laboratory Test and Study and Numerical Calculation and Analysis for Characteristics of Expansive Soil at Macha River - ZHANG Tianqi; HOU Li; XING Jinglian; ZHANG Yin (Renmin Zhujiang)
Expansive soil is one of the unfavorable factors leading to slope instability, so it is essential to study its characteristics. This paper analyzes the variation rules of basic physical properties such as free expansion rate and water content with soil depth and studies the variation rules of crack and strength of expansive soil through physical parameter test at laboratory and wetting-drying test of undisturbed soil, as well as calculates and analyzes the sensitivity of upstream slope ratio, height and width of embankment on its safety and stability based on a numerical calculation model. The results show that: the moisture content of expansive soil at Macha River is mainly about 20%, and the soil is in hard plastic state;with isobathic distribution along the slope, the distribution of expansive soil layer is inconsistent with that of geological soil layer; with the increase of the number of wetting-drying cycles, the large cracks appear on the sample and gradually form a network for damage after about 4 wetting-drying cycles; its cohesion c and internal friction angle φ also decreased in the process of wetting-drying cycles, and the strength parameters of expansive soil basically become stabilize after 8 wetting-drying cycles;the safety factor of expansive soil slope is in direct proportion to the upstream slope ratio and embankment width and in inverse proportion to embankment height;after 4 or 5 wetting-drying tests, its safety factor decreases at the fastest speed, with drop-out value accounting for about 83% of the initial safety factor, which provide reference for slope design in expansive soil area.